Metal oxide‐based gas sensors for the detection of exhaled breath markers. Issue 1 (29th March 2021) - Vajhadin, Fereshteh; Mazloum‐Ardakani, Mohammad; Amini, Abbas
Abstract: Exhaled breath test is a typical disease monitoring method for replacing blood and urine samples that may create discomfort for patients. To monitor exhaled breath markers, gas biomedical sensors have undergone rapid progress for non‐invasive and point‐of‐care diagnostic devices. Among gas sensors, metal oxide‐based biomedical gas sensors have received remarkable attention owing to their unique properties, such as high sensitivity, simple fabrication, miniaturization, portability and real‐time monitoring. Herein, we reviewed the recent advances in chemoresistive metal oxide‐based gas sensors with ZnO, SnO2 and In2 O3 as sensing materials for monitoring a range of exhaled breath markers (i.e., NO, H2, H2 S, acetone, isoprene and formaldehyde). We focused on the strategies that improve the sensitivity and selectivity of metal oxide‐based gas sensors. The challenges to fabricate a functional gas sensor with high sensing performance along with suggestions are outlined.